3 - Zone franc, sous-développement et dépendance en Afrique noire francophone - Guy Martin, (Africa Development, 1987)
The Franc zone is a monetary cooperation arrangement set up between France and her former colonies in West and Centrât Africa following the latter's independence in the early sixties. While thi system is central to an understanding of these African countries' dependence on France, it has been the object of surprinsingly few scientific studies. Indeed, most of the literature on the subject is heavily biased in favour of the system. The present study - which identifies with a neo-radical trend of critical scholarship on the subject - is an attempt to take a dispassionate and objective look at the facts. Using dependency theory, this article analyzes the origins, structure and functioning of the Franc zone system and assesses its legal, political and economic consequences for the African member states. The evidence suggests that contrary to the prevailing view, the Franc zone, far from contributing to the economic development and independence of its African member states, is largely instrumental in perpetuating and increasing these states' underdevelopment and dependency on France